1976
DOI: 10.1021/ja00436a009
|View full text |Cite
|
Sign up to set email alerts
|

Stabilities and energetics of pentacoordinated carbonium ions. The isomeric protonated ethane ions and some higher analogs: protonated propane and protonated butane

Abstract: The kinetics and equilibria of reaction 1 were studied in H2 gas at 1-5 Torr over the temperature range -160 to 200 °C. The experiments were done in a pulsed electron beam high pressure ion source mass spectrometer. At the lowest temperatures (-160 to -130 °C) reaction 1 reached equilibrium. The forward rate of (1) decreased with increasing temperature. This means that the C2H7+(a) formed at this temperature was a result of an exothermic third body dependent reaction without activation energy. Measurement of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
67
1
3

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(83 citation statements)
references
References 10 publications
12
67
1
3
Order By: Relevance
“…[34] This product forms through trapping of the exo-4-substituted tetracyclo[3.3.0.0 2,8 .0 3,6 ]oct-7-yl cationic structure with the reagent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[34] This product forms through trapping of the exo-4-substituted tetracyclo[3.3.0.0 2,8 .0 3,6 ]oct-7-yl cationic structure with the reagent.…”
Section: Methodsmentioning
confidence: 99%
“…
Protonation of saturated hydrocarbons is the simplest and practically most important electrophilic reaction.[1] Small alkanes like methane, ethane, and isobutane [2] form welldefined protonated species, and their experimental proton affinities (PAs) are excellently reproduced computationally. [3][4][5] However, the current data on the protonations of strained hydrocarbons are rather controversial, and facile rearrangements are thought to account for the difficulties encountered in measuring the PAs.

[6] Cyclopropane (strain energy(E str ) = 27.2 kcal mol À1 ) is an exception because the number of energetic downhill paths is very limited and the barrier for the ring opening of corner-protonated C 3 H 7 + to the 2-propyl cation is high.

…”
mentioning
confidence: 99%
“…High-pressure mass spectrometric studies on size-selected C 2 H 5 + ·L n clusters (e.g., L = OCS, CO 2 , N 2 O, CH 4 , N 2 , H 2 , noble gas) [16] demonstrated mainly formation of weakly bound aggregates without reaction, with binding enthalpies between about 7 (L = Ar) and about 50 kJ mol À1 (L = N 2 O). [17] However, no structural information on the C 2 H 5 + ion core could be obtained, although accompanying quantum chemical calculations suggested that the geometry of C 2 H 5 + sensitively depends on the type of solvent and the degree of solvation.…”
mentioning
confidence: 99%
“…A useful experimental approach consists in the determination of the dissociation energy of the carbonium ions by ion-equilibrium measurements, as performed by Kebarle and Hiraoka using high-pressure ion source mass spectrometry [14]. The thermodynamics of the protonation of alkanes and the energetics of pentacoordinated alkyl carbonium ions are not easily accessible experimentally, but they are linked through the dissociation energy of the carbonium ions to the energetics of the corresponding carbenium ions that can more readily be studied experimentally.…”
Section: 5mentioning
confidence: 99%